DESKRIPSI KUALITAS PELAYANAN KESEHATAN UNIT RAWAT INAP DI RUMAH SAKIT: 5 DIMENSI SERVSQUAL - Valentine Kenya Wahyu Khuntari; Hendra Dwi Kurniawan; Sri Aminingsih; Ditya Yankusuma Setiani (An Nafi': Multidisciplinary Science, 2025)
Health services are efforts organized to maintain and improve public health, as well as prevent and cure diseases. Hospitals as public health institutions play an important role in providing quality health services. However, the quality of health services in hospitals often comes under scrutiny, especially in the context of inpatient services. This study focuses on the five dimensions of service quality according to the servsqual model, namely reliability, responsiveness, assurance, empathy and tangibility. In Indonesia, there has been an increase in the number of people choosing to seek treatment abroad, indicating dissatisfaction with domestic health services. This indicates the need for an in-depth evaluation of the quality of health services provided, especially in inpatient units. Research Objectives. The purpose of this study was to determine the description of health service quality based on 5 dimensions of servsqual. This study is a quantitative study with a descriptive design through a cross sectional approach. The population in this study were inpatients of the Tjan Khee Swan East and Asa buildings. The number of samples in this study were 70 respondents. The sampling technique used consecutive sampling. The results showed that the quality of service is good from the dimensions of reliability (62.9%), responsiveness (61.4%), assurance (68.6%), empathy (67.1%), tangible (64.3%). Service quality with the dimensions of reliability, responsiveness, assurance, empathy, tangible is categorized as good.